2007
DOI: 10.2478/s11536-006-0043-6
|View full text |Cite
|
Sign up to set email alerts
|

Wheezing and lung function measured in subjects exposed to various levels of fine particles and polycyclic aromatic hydrocarbons

Abstract: AbstractThe main purpose of the study was to assess the occurrence of wheezing and lung function in non-smoking women exposed to various levels of fine particulate matter(FP) and polycyclic aromatic hydrocarbons (PAH). Out of the total study group, 152 women were included in the lower exposed group (PM2.5 ≤34.3μg/m3 or PAHs ≤ 22.9ng/ m3) and 96 persons in higher concentrations of both air pollutants (PM2.5>34.3μg/m3 and PAHs > 22.9ng/ m3). Except for FVC and FEV1, all lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
6
1
Order By: Relevance
“…Combined gas and particle PAH concentrations measured in German bars measured were 278.5 ng/m 3 , restaurants 220.6 and dance clubs 392.6 ng/m 325 compared to 1325.1 ng/m 3 in this study. In addition the values reported in this study greatly exceed the PAH concentration of 22.9 ng/m 3 determined by Jedrychowski14 to cause an increase in wheeze and a decrease in lung function in their study population of adults. It is important to highlight that the levels in this study are 1-h averages while the comparison values are at least 8 h averages.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Combined gas and particle PAH concentrations measured in German bars measured were 278.5 ng/m 3 , restaurants 220.6 and dance clubs 392.6 ng/m 325 compared to 1325.1 ng/m 3 in this study. In addition the values reported in this study greatly exceed the PAH concentration of 22.9 ng/m 3 determined by Jedrychowski14 to cause an increase in wheeze and a decrease in lung function in their study population of adults. It is important to highlight that the levels in this study are 1-h averages while the comparison values are at least 8 h averages.…”
Section: Discussioncontrasting
confidence: 75%
“…However tobacco smoke is comprised of thousands of constituents including polycyclic aromatic hydrocarbons (PAH). PAH exposures have been shown to cause immunological changes,13 and have been associated with wheeze and changes in IQ14 as well as allergic sensitisation 15. The PAH concentrations measured in our study are to our knowledge the first to be reported inside a vehicle with an active cigarette smoker.…”
Section: Introductionmentioning
confidence: 57%
“…17,18 PAHs have also been associated with lower pulmonary function and wheezing in adults. 19 One study of community-level air pollution compared the average pulmonary function across two communities with different concentrations of ambient air pollutants, including PAHs, 7 but no previous study of individual PAH exposure and pulmonary function in children has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…PAHs and other anthropogenic oxidants are hypothesized to affect the risk for asthma by causing bronchial inflammation and bronchoconstriction (Jedrychowski, et al, 2007). There is evidence to suggest that PAHs act through the immunoglobulin E (IgE) (Tsien, DiazSanchez, Ma and Saxon, 1997) pathway to stimulate inflammatory responses (Nel, Diaz-Sanchez, Ng, Hiura and Saxon, 1998) and enhance allergic inflammation (Lubitz, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%